A influência do traçado de mobilidade na noção de território e nas oportunidades de desenvolvimento local - Liliana Cunha; Marianne Lacomblez (Universidade do Porto, 2008)
Mobility is often discussed as a vector of economic development and as a structural dimension of social integration. Less visible, apparently, has been the discussion of the mobility projects through public transport; of the criteria on which they are based and of what they predict in terms of local development. The interrogation of this connection is our guide, also considering the intention of those who participate in the design of the transport networks; the perspective of those who provide the service; and the territorial specificities. In the wake of two concrete examples, referring to two different realities - in Portugal, in a rural context, and in Mozambique, in an urban context - it is possible to see how the concentration of activities, especially economic ones, is a key factor to the constructed dynamics of mobility.The debate takes place in the territorial asymmetries, fostered by centralized development projects and in the need for another approach to mobility, for which this article outlines some contributions.